Analysis of the Mastery of Arabic Morphology by Students in Reading Arabic Texts: Analisis Penguasaan Morfologi Bahasa Arab oleh Siswa dalam Membaca Teks-teks Bahasa Arab - Siti Sholehah Doholio; Mukhtar I. Miolo; Fouad Achir (ELOQUENCE : Journal of Foreign Language, 2026)
Background: Mastery of Arabic morphology is one of the important foundations in learning Arabic, especially in the context of reading Arabic texts, which is a major requirement for students at Islamic boarding schools. However, the extent to which mastery of morphology contributes to proficiency in reading Arabic texts still needs to be studied empirically in order to provide a more effective basis for teaching. Objective: This study aims to analyze the relationship between mastery of Arabic morphology and the Arabic text reading proficiency of students in Islamic boarding schools. Method: This study uses a quantitative approach with a correlational design. Data were collected through objective tests that measured morphology mastery and Arabic text reading ability in 60 students (N = 60) from one selected Islamic boarding school. Data analysis was performed using Pearson's correlation test to determine the strength and direction of the relationship between the two variables. Results and Discussion: The results of Pearson's correlation test showed a positive relationship with moderate to strong strength between Arabic morphology mastery and Arabic text reading proficiency, with a correlation coefficient of r = 0.534. (R² = 0.285, indicating that morphology mastery accounted for 28.5% of the variance in Arabic text reading proficiency; this represents a large effect size according to Cohen's (1988) classification, 95% CI [0.32, 0.69]). This relationship is unidirectional, meaning that the higher the mastery of morphology, the better the ability to read Arabic texts. The significance value p = 0.000 (p < 0.01) indicates that the correlation is statistically significant at the 1% level. These findings reinforce the role of morphology as an important component in the development of students' Arabic literacy, even though it is not the only factor.